O-009 Data from the ESHRE PGT consortium – year 2019. (6th August 2021) - Van Montfoort, A; De Rycke, M; Carvalho, F; Rubio, C; Bronet, F; Spinella, F; Goossens, V
Abstract text: Study question: Which are the trends shown in data collection XXI of the European Society of Human Reproduction and Embryology (ESHRE) PGT Consortium compared with previous years? Summary answer: Data collection XXI, year 2019, represents valuable data on PGT activity in (mainly) Europe and reports on the main trends observed, being the further expansion of comprehensive testing technology in PGT-SR and PGT-A. What is known already: The ESHRE PGT Consortium was set up in 1997 and from that time has been collecting data on PGT and PGT-A. The PGT database comprises the world's largest collection of PGT / PGT-A data providing a valuable resource for data mining and for following trends in PGT practice. So far, up to the year 2015, data collections were carried out in a retrospective data way, from 2016 onwards a prospective data collection was in place. Study design, size, duration: As the nature of PGT/ PGT-A treatments has changed significantly over the last years and IVF cycle management and genetic analysis techniques are getting more complex, ESHRE uses an online data collection system in which data are collected prospectively from oocyte retrieval to analysis, embryo transfer and pregnancy / live birth. Data are collected cycle by cycle on a voluntary basis. Participants/materials, settings, method: For the 2019 data, individual centres (31) from 19 countries directly entered the data into the PGT database through software developed by ESHRE. Data were analysed at ESHRE headquarters and include all aspects of PGT/PGT-A cycles. Main results and the role of chance: The Consortium has analysed the PGT analyses (n = 2735) performed in 2019. The indications for PGT included inherited chromosomal abnormalities (n = 253 analyses), monogenic disorders (n = 1105 analyses), aneuploidy testing for infertility (n = 1111 analyses) or combinations of the above (n = 266 analyses). In addition, 662 clinical pregnancies and 216 deliveries have been analysed in detail. The methods used for biopsy were polar body (2%), cleavage stage biopsy (35%) and blastocyst biopsy (61%; comparable with data from 2018). The methodology used for diagnosis is what is evolving most over the last years, with data set XXI (2019) showing around 7% of FISH, 37% of PCR and 55% of WGA. Within WGA 90.6% of the analysis were done using NGS, in 4.4% cases SNP arrays were used and in 2.4% array-CGH was used. The overall clinical pregnancy rate is about 24% per analysis. The baby data show that it is difficult for most centres to have a detailed follow-up. Limitations, reasons for caution: The findings apply to the 31 participating centres and may not represent worldwide trends in PGT. Data were collected prospectively, but details of the follow-up on PGT pregnancies and babies born were limited. Wider implications of the findings: The ESHRE PGD Consortium continues its activities as an important forum for PGT practitioners to share data and exchange experiences. The information extracted from the data collections helps to monitor quality issues in PGT and survey the introduction and effectiveness of new PGT technologies and methods.